Apps for pain self-management of older people's arthritic pain, one size doesn't fit all: A qualitative study. (July 2020) - Bhattarai, Priyanka; Newton-John, Toby R.O.; Phillips, Jane L.
Highlights: Apps have the potential to add value to older people's arthritic pain self-management process. Older people expect a useful pain self-management app to include focused and relevant content with customisation feature. The possibility of information and assessment data exchange with clinicians via an app was welcomed by older people. Abstract: Introduction Arthritic pain is a major cause of illness and disability among older people. People living with arthritic pain carry out self-management activities to adequately manage their pain. As the trend of smartphone uptake continues to rise among older people, there are opportunities to explore the role of these devices in helping older people better manage their pain. Aim: To explore the attitudes and experiences of older people with chronic arthritic pain towards using an app for their pain selfmanagement. Methods A qualitative design using semi-structured interviews with community-dwelling older Australians living with arthritic pain (n = 16). Data was analyzed using thematic analysis. Results Four themes emerged from the data: (1) Apps are valuable self-management tool, but they do have the potential for harm; (2) A pain self-management app needs to strictly align with the user's needs; (3) Clinician's involvement is crucial when integrating an app into older people's pain selfmanagement regime; and (4) pain self-management app must be designed with enduser in mind. In addition, suggestions on how to make an app more useful and userfriendly were offered by the participants. Discussion While pain self-management apps have the potential to assist older people in their pain self-management process, this modality is not of interest to all older people. Adaptable apps that offer clinician input may be best placed to offer individual level relevance to older users. Future pain selfmanagement app development endeavors should adopt a co-design approach where older people are involved through all stages of design and development.